A computational investigation of the selectivity and mechanism of the Lewis acid catalyzed oxa‐Diels–Alder cycloaddition of substituted diene with benzaldehyde. Issue 18 (30th April 2021) - Khorief Nacereddine, Abdelmalek; Merzoud, Lynda; Morell, Christophe; Chermette, Henry
Abstract: The selectivity and the mechanism of the uncatalyzed and AlCl3 catalyzed hetero‐Diels–Alder reaction (HDR) between ([E]‐4‐methylpenta‐2, 4‐dienyloxy)(tert‐butyl)dimethylsilane 1 and benzaldehyde 2 have been studied using density functional theory at the MPWB1K/6‐31G(d) level of theory. The uncatalyzed HDR between diene 1 and alkene 2 is characterized by a polar character and proceeds via an asynchronous one‐step mechanism for the meta paths and synchronous for the ortho ones. In the presence of AlCl3 catalyst, the mechanism changes to be stepwise, while the first step is the rate‐determining step. The activation energies widely decrease, and the polar character increases dramatically. A large analysis of the mechanism is performed using the activation strain model/energy decomposition analysis (ASM/EDA) model, the natural bond orbital (NBO) and state specific dual descriptors (SSDDs). The obtained results indicate that the combined interaction energy associated with the distortion of the reactants in these HDR are at the origin of the observed kinetics. NBO analyses were applied to estimate the Lewis‐acid catalyst donor‐acceptor interaction with the molecular system. The SSDD analysis shed light into the orientation effects on the reaction kinetics by providing important information about charge transfer interactions during the chemical reaction. It indicates that the more favorable HDR pathway have the lowest excitation energies, facilitating the interaction between diene 1 and benzaldehyde 2 moieties. Non‐covalent interaction (NCI) and QTAIM analyses of the meta‐endo structure indicate that the presence of several weak NCIs formed at this approach is at the origin of the meta‐endo selectivity. Abstract : A mechanistic study on the uncatalyzed and AlCl3 ‐catalyzed hetero‐Diels–Alder reaction between diene and benzaldehyde is performed, making use of conceptual quantum chemical tools. The relation between activation energies and intermolecular excitations is rationalized, and factors driving reactivity and regioselectivity are highlighted.